Ventilator-Associated Pneumonia in Neurosurgical Patients: A Tertiary Care Center Study - Shrestha, Dipendra K; Rajbhandari, Binod; Pradhanang, Amit; Sedain, Gopal; Shilpakar, Sushil K; Pradhan, Saurav (Journal of Institute of Medicine Nepal, 2019)
Introduction: Ventilator-associated pneumonia (VAP) is a well recognized complication in patients who are admitted to the Intensive Care Unit (ICU). A number of factors have been suspected or identified to increase the risk of VAP in Neurosurgical patients. Early and rapid diagnosis and initiation of the appropriate antibiotic treatment reduce mortality and decrease the development of MDR organisms. The aim of our study is to determine the incidence of VAP in the neurosurgical patients and also to assess the probable contributing neurosurgical risk factors and find out the causative bacterial pathogens and the resistant pattern of these bacteria in neurosurgical patient in ICU of our institute Methods: A retrospective observational study of 106 neurosurgical patients who were on mechanical ventilation for more than 48 hours was done. Results: Out of 106 patients, 35 patients fulfilled the clinical and microbiological criteria for the diagnosis of VAP. The commonest age group involved was between 15-25 years of age with male preponderance. Head injury was the commonest etiology. There was a linear correlation between the number of days in ICU and the development of VAP. The majority of the pathogen isolated were gram-negative bacteria and all were sensitive to Colistin. Conclusion: Head injury is a significant risk factor for VAP. Prolonged mechanical ventilation is an important risk factor for VAP.